Triple‐Targeting Delivery of CRISPR/Cas9 To Reduce the Risk of Cardiovascular Diseases. Issue 36 (1st August 2019) - Zhang, Lingmin; Wang, Le; Xie, Yangzhouyun; Wang, Peng; Deng, Sai; Qin, Aiping; Zhang, Jiangjiang; Yu, Xiyong; Zheng, Wenfu; Jiang, Xingyu
Abstract: A high level of low‐density lipoprotein cholesterol (LDL‐C) in the blood is a major risk factor for coronary heart disease. Herein, we present a triple‐targeting strategy to generate a loss‐of‐function mutation in Pcsk9, which regulates plasma cholesterol levels, using a nanocarrier‐delivered CRISPR/Cas9 system. Nuclear localization signal (NLS)‐tagged Cas9 and Pcsk9 ‐targeted single guide RNA (sgPcsk9) were complexed with gold nanoclusters (GNCs) modified with cationic HIV‐1‐transactivating transcriptor (TAT) peptide and further encapsulated in a galactose‐modified lipid layer to target the nanoclusters to the liver. The resulting nanoclusters had an in vitro Pcsk9 ‐editing efficiency of about 60 % and resulting in a decrease in plasma LDL‐C in mice of approximately 30%. No off‐target mutagenesis was detected in 10 sites with high similarity. This approach may have therapeutic potential for the prevention and treatment of cardiovascular disease without side effects. Abstract : A gold‐nanocluster‐based CRISPR/Cas9 delivery system could deliver CRISPR/Cas9 to the liver of mice, mutating the Pcsk9 gene and decreasing low‐density lipoprotein cholesterol (LDL‐C) levels in the plasma. This approach uses galactose to target the asialoglycoprotein receptor (ASGPR) on hepatocytes, and the HIV TAT peptide and a nuclear localization signal to target nuclei, and may be useful for the prevention and treatment of cardiovascular disease.